THE INFLUENCE OF LEADERSHIP STYLE ON EMPLOYEE PERFORMANCE AND WORK MOREST THROUGH WORK MOTIVATION INTERVENING VARIABLES AT CV. PRIMA PRICE - Azhari, Saiful; Rafiki, Ahmad; Effendi, Ihsan (UNIVERSITAS PAKUAN, 2025)
This research aims to analyze the influence of leadership style and work enthusiasm on employee performance, with work motivation as an intervening variable. The study employs a quantitative research approach, utilizing Structural Equation Modeling Partial Least Squares (SEM-PLS) for data analysis. The research was conducted at CV. Harsa Prima, a company engaged in multimedia technology, with a total sample of 42 employees. The findings indicate that leadership style positively affects work motivation, with a coefficient value of 0.609, and also positively impacts employee performance, with a coefficient value of 0.375. Additionally, work motivation has a positive effect on employee performance, with a coefficient value of 0.442. Furthermore, leadership style positively influences work morale, with a coefficient value of 0.44, while work motivation also significantly impacts work morale, with a coefficient value of 0.51. The study further reveals that work motivation significantly mediates the relationship between leadership style and work morale, as indicated by a T-statistic of 1.862 (>1.647) and a P-value of 0.032 (1.647) and a P-value of 0.036 (